2017
DOI: 10.1111/joic.12484
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after drug‐coated balloon treatment for patients with calcified coronary lesions

Abstract: Calcified coronary lesions might dilute the effect of DCB. However, clinical outcomes in the calcified group were similar to those in the non-calcified group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
0
15
1
Order By: Relevance
“…Ito et al reported a restenosis incidence of 13.9% at 6.5 months, late lumen loss of 0.03 mm, and late lumen enlargement of 47.2% after DCB for patients with de novo calcified coronary lesions using QCA (RA was used in 82% of cases), in accord with the present study. However, it should be noted that the present study enrolled restenosis cases including ISR as well as de novo lesion cases [18]. Intracoronary imaging modalities such as OFDI, OCT, and IVUS have facilitated PCI development by expanding our understanding of coronary calcium placing and wire bias.…”
Section: Discussionmentioning
confidence: 99%
“…Ito et al reported a restenosis incidence of 13.9% at 6.5 months, late lumen loss of 0.03 mm, and late lumen enlargement of 47.2% after DCB for patients with de novo calcified coronary lesions using QCA (RA was used in 82% of cases), in accord with the present study. However, it should be noted that the present study enrolled restenosis cases including ISR as well as de novo lesion cases [18]. Intracoronary imaging modalities such as OFDI, OCT, and IVUS have facilitated PCI development by expanding our understanding of coronary calcium placing and wire bias.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that compared outcomes of the treatment of de novo coronary artery lesions with DCB and nDES showed similar safety and long-term efficacy [5, 6]. In addition, we recently reported that the clinical outcomes after DCB treatment of moderate or severe calcified lesions and noncalcified lesions were similar [7].…”
Section: Introductionmentioning
confidence: 92%
“… 14 , 15 , 16 A recent report from Japanese investigators has indicated that among de novo coronary lesions with a mean reference diameter of 2.22 mm, angiographic and clinical outcomes of DCB-based stentless PCI in the noncalcified lesions were comparable with those in the calcified lesions. 17 As for large vessel de novo lesions, a single report has shown that DCB-based stentless PCI is safe and effective even among coronary arteries (> 2.75 mm) with average reference diameter of 3.16 mm and calcification frequency of approximately 20%. 18 The noncalcified lesions tended to have a larger reference diameter and a shorter lesion length than the calcified lesions, which might account for the difference in the distribution of the guiding catheter size between the noncalcified and calcified lesions in the present study.…”
Section: Discussionmentioning
confidence: 99%